CT number changes within depth in CT and CBCT images - Junit, Syarifah Nurfajrina Syed (Universiti Sains Malaysia, 2015)
This study was carried out to determine the effect of increased depth to CT number on CT and CBCT images. In addition, this study was done to establish scanning method on CT and CBCT modalities in order to provide more precise dosimetry calculation involving CT and CBCT. An electron density phantom with tissue equivalent plugs was used in this study. The plug phantoms of various tissue equivalent materials were placed at different depths between the centre and peripheral of the phantom and scanned using CT and CBCT modalities. Images for both modalities were acquired and CT numbers at different depth in the phantom were analyzed. The results showed that on CT images, water equivalent plug phantom showed highest changes of CT number from peripheral position to central position with 146.4% and the lowest was air cavity with 0.55%. The results in CBCT images showed that muscle tissue equivalent plug phantom gave the highest change of CT number at increased depth with 6842.17% and the lowest difference was given by dense bone tissue equivalent plug phantom with 11.72%. A comparison of change in CT number between CT and CBCT showed that CBCT images having higher rate of change of CT number from peripheral position to central position compared to that in CT images. As conclusion, the CT number was found to be significantly increase as the depth increased. Thus, dosimetry measurement using CT number is suggested to be done at central position of phantom considering the contribution of x-ray scattering to the point of measurement. A calibration of CT number is required for dosimetry measurement at positions nearer to the surface of medium.